2016
DOI: 10.17795/jjcdc-37038
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Sexual Function in Females of Reproductive Age Referred to Rural and Urban Healthcare Centers in Ahvaz, Iran

Abstract: Background: Healthy sexual function can be considered as an important element to improve personal and public hygiene. The sexual desire plays an important role in mental health and improving the quality of life. Objectives: The current study aimed to compare sexual function of females in urban and rural areas. Methods: The current descriptive study adopted 800 females of reproductive age (range 15 -45 years) referred to rural and urban healthcare centers in Ahvaz, Iran, in 2015. Samples were randomly selected.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
1
0
0
Order By: Relevance
“…➔Our findings showed that, arousal and lubrification sub-scales, as well as the global sexual functioning were significantly higher in urban women. This was consistent with previous studies [8]. This difference in female sexuality between urban and rural areas may reflect socio-cultural representations.…”
Section: Discussionsupporting
confidence: 93%
“…➔Our findings showed that, arousal and lubrification sub-scales, as well as the global sexual functioning were significantly higher in urban women. This was consistent with previous studies [8]. This difference in female sexuality between urban and rural areas may reflect socio-cultural representations.…”
Section: Discussionsupporting
confidence: 93%